Det dubbla statushandikappet och sjukförsäkringens moraliska praktiker : en aktstudie om sjukpenningärenden som får negativa beslut på Försäkringskassan - Hultgren, Peter (Linnéuniversitetet, Institutionen för samhällsvetenskaper, SV, 2011)
In recent years an increasing number of sickness allowance cases have been closed with a negative decision despite the fact that a certifying doctor has recommended sick leave. At Social Insurance Offices, a case file is established for each sickness allowance case. The case files for 538 rejected cases form the basis for this study.   The assessment of the entitlement to sickness allowance is a key instrument of control in the health insurance system and the sharpened borderline between the obligation to work and the entitlement to sickness allowance can be interpreted as the result of a political aim to promote work through the health insurance system. This thesis explores these demarcation practices, highlighting the ways in which this policy of work promotion is translated into and made manifest in real world cases.   Three aspects of these practices were highlighted in the study described in the thesis. The first aspect concerns the identification of those who are denied sickness allowance; their diagnoses and work situations. The second aspect relates to the interaction between the certifying doctor, the medical officer and the case officer and their respective roles in the process leading to negative decisions. The third aspect examines how the actors interpret and apply the concepts of sickness and ability to work in cases with negative decisions. In addition to these themes, in the final chapter of the thesis, I draw on theories of institutionalised organisations and moral practices to analyse the outcomes of the decision-making process.   The thesis shows that a negative decision is most likely to be applied to insured persons who are either unemployed or who are manual workers without educational qualifications, and who have received diagnoses of mental illhealth or of diagnoses of pain and ache problems in the locomotive organs. It is argued that this is a moral category formed through the interaction of government policy dictates promoting work with actors, who in their official roles must apply an extremely vague criterion for entitlement to social insurance, namely disablement caused by illness.  In this way, the dual handicap  – undervalued labour (market) position plus undervalued gravity of illness – has become a borderline marker when the right to sickness allowance is being investigated and contested.